Community Service in Assisting Culinary Students of STU Tangeb, Abianbase Village, Mengwi, Badung Regency in Producing Innovative Bakery Products - Semariyani, A.A.Made; Mangku, I Gede Pasek; Sugiana, I Gusti Ngurah (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
This community service activity was carried out to assist Culinary students at STU Tangeb in producing innovative bakery products, aiming to broaden their knowledge of bakery production, including raw materials, processing, packaging and labelling, industrial management, digital marketing, and procedures for obtaining production permits (PIRT). The methods used in this program included interviews to identify problems and the direct participation of partners in the production of various bakery products (such as Danish pastry, pizza, flavoured sweet bread, sponge cake, chiffon cake, and brownies), packaging and labelling, bookkeeping, and digital marketing. The objective of this program was to provide solutions to the problems faced by partners in innovative bakery production, financial bookkeeping, marketing, and licensing (PIRT). The results of the programme show that partners acquired skills in producing innovative bakery products (with various variations/creations). Print and electronic media have published this community service activity, and YouTube has also uploaded the video documentation. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 12: Responsible Consumption And Production